2014
DOI: 10.1017/s1366728914000273
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility in task switching by monolinguals and bilinguals

Abstract: Many bilinguals routinely switch between their languages, yet mixed evidence exists about the transfer of language switching skills to broader domains that require attentional control such as task switching. Monolingual and bilingual young adults performed a nonverbal task-switching paradigm in which they viewed colored pictures of animals and indicated either the animal or its color in response to a cue. Monolinguals and bilinguals performed similarly when switching between tasks (local switch cost) in a mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 39 publications
(55 reference statements)
5
76
1
3
Order By: Relevance
“…Similar results with respect to decreased task switch costs (Barac & Bialystok, 2012;Prior & MacWhinney, 2010) and task mixing costs (Wiseheart, Viswanathan, & Bialystok, 2015) were found between bilinguals and monolinguals. These results indicate that long-term language switching training can have a substantial influence on task switching and thus indicates that there is an apparent link between the two switching tasks.…”
Section: Processing Stages Outside Of Language Processingsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar results with respect to decreased task switch costs (Barac & Bialystok, 2012;Prior & MacWhinney, 2010) and task mixing costs (Wiseheart, Viswanathan, & Bialystok, 2015) were found between bilinguals and monolinguals. These results indicate that long-term language switching training can have a substantial influence on task switching and thus indicates that there is an apparent link between the two switching tasks.…”
Section: Processing Stages Outside Of Language Processingsupporting
confidence: 79%
“…These results indicate that long-term language switching training can have a substantial influence on task switching and thus indicates that there is an apparent link between the two switching tasks. Yet, not all studies found smaller task switch costs for bilinguals than monolinguals (e.g., Hernández, Martin, Barceló, & Costa, 2013;Paap & Greenberg, 2013;Wiseheart et al, 2015).…”
Section: Processing Stages Outside Of Language Processingmentioning
confidence: 99%
“…In fact, some have suggested that mixing costs is where one would most expect bilingual advantages to arise—given that actual switches are relatively rare events, but the possibility to need to mix languages is always present when bilinguals are speaking (Prior & Gollan, 2013; Wiseheart et al, 2014; Bialystok et al, 2009 for review). Following this logic, Barac and Bialystok (2012) used the color-shape switching task with three groups of six-year old bilingual children (Chinese-English, French-English, and Spanish-English) and found smaller mixing, but not switching, costs for all bilingual groups relative to monolingual children.…”
Section: Discussionmentioning
confidence: 99%
“…Another indication of a link between bilingual language use and EC processing can be found in those studies that compared monolinguals and bilinguals performing EC tasks (e.g., Bialystok & Martin, 2004;Bialystok & Viswanathan, 2009;Prior & MacWhinney, 2010;Tao, Marzecová, Taft, Asanowicz, & Wodniecka, 2011;Costa, Hernández & Sebastián-Gallés, 2008;Costa, Hernández, Costa-Faidella, & Sebastián-Gallés, 2009;Wiseheart, Viswanathan, & Bialystok, 2016). In fact, some of these studies revealed that the continuous use of two languages affect the cognitive processes related to domain-general EC, such as those put at play during non-linguistic switching tasks (e.g., Prior & MacWhinney, 2010;Prior & Gollan, 2011;Prior, 2012;Wiseheart, et al, 2016), thereby suggesting a certain functional overlap between those processes involved in linguistic and non-linguistic domains of cognitive control.…”
Section: Introductionmentioning
confidence: 93%
“…In fact, some of these studies revealed that the continuous use of two languages affect the cognitive processes related to domain-general EC, such as those put at play during non-linguistic switching tasks (e.g., Prior & MacWhinney, 2010;Prior & Gollan, 2011;Prior, 2012;Wiseheart, et al, 2016), thereby suggesting a certain functional overlap between those processes involved in linguistic and non-linguistic domains of cognitive control. Despite these findings have motivated recent research to focus on the extent of this overlap (e.g., Calabria et al, 2012;Weissberger et al, 2012;Cattaneo et al, 2015;Coderre, Smith, van Heuven, & Horwitz, 2015;6 Weissberger, Gollan, Bondi, Clark, & Wierenga, 2015;De Baene, Duyck, Brass, & Carreiras, 2015), other recent findings have strongly undermined the basic assumption of the existence of an overlap between bLC and EC (e.g., Paap et al, 2013;Hernandez et al, 2013;Paap & Sawi, 2014;Duñabeitia, Hernández, Antón, Macizo, Estévez, Fuentes & Carreiras, 2014;Kousaie, Sheppard, Lemieux, Monetta, & Taler 2014;Antón, Duñabeitia, Estévez, Hernández, Castillo, Fuentes, Davidson, & Carreiras, 2014;von Bastian, Souza, Gade, 2015).…”
Section: Introductionmentioning
confidence: 99%